2023
DOI: 10.1177/00405175221148263
|View full text |Cite
|
Sign up to set email alerts
|

A review of wearable carbon-based sensors for strain detection: fabrication methods, properties, and mechanisms

Abstract: Carbon-based flexible wearable sensors have received widespread attention due to their wide application in wearable electronics. This work reviewed the different carbon-based sensors from three aspects, such as fabrication, performance and working mechanisms. Carbon materials mainly included carbon nanotubes, graphene, carbon black and other carbon materials. In particular, carbon nanotubes and graphene can be assembled into various multiscale macrostructures to prepare various forms of flexible sensors, such … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 77 publications
0
9
0
Order By: Relevance
“…It is directly proportional to the fermi energy from their mathematical relationship where the proportionality constant is − 1. It is also a suitable indicator that provides a better understanding of the reactivity and sensitivity of nanostructures towards adsorption of different molecules 70 , 71 . From the Table 5 , the work function values ranged from − 3.279 to − 8.191 eV.…”
Section: Resultsmentioning
confidence: 99%
“…It is directly proportional to the fermi energy from their mathematical relationship where the proportionality constant is − 1. It is also a suitable indicator that provides a better understanding of the reactivity and sensitivity of nanostructures towards adsorption of different molecules 70 , 71 . From the Table 5 , the work function values ranged from − 3.279 to − 8.191 eV.…”
Section: Resultsmentioning
confidence: 99%
“…There has been a lot of research that focuses on the development of carbonbased strain sensors for physiological-signal monitoring. For more details, readers may consult the following recent reviews [16,17]. Strain sensors work by converting signals of mechanical deformation into electrical signals.…”
Section: Carbon-based Textile Sensors For Body Motion Monitoringmentioning
confidence: 99%
“…Recently, several reviews have been reported of wearable flexible sensors for physiologicalsignal monitoring [16][17][18]. However, most reviews focus on the development of carbonbased strain sensors for physiological-signal monitoring [16,17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results show that the biscrolled HGSP yarn exhibits a rapid response time and high sensitivity to flammable H 2 concentrations, and it can even detect H 2 gas leakage in curved and jointed areas in real time. Zhang et al [ 29 ] conducted a review of carbon-based flexible wearable sensors and their fabrication, performance, and working mechanisms. The study concluded that CNTs and graphene can be added to various macrostructures to create flexible sensors in the form of films, fibers, yarns, or fabrics.…”
Section: Introductionmentioning
confidence: 99%